Pengaruh Kepemimpinan Transformatif Terhadap Peningkatan Sumber Daya Manusiadi Kantor Desa Seberang Kabupaten Bone - Syam, Marniati; Syafitri, H. Mursakin Dwigita (YUME : Journal of Management, 2024)
This research aims to find out whether Transformative Leadership has a significant effect on increasing Human Resources at the Seberang Village Office, Lamuru District, Bone Regency. This research uses a quantitative descriptive research method which aims to create an objective picture or description of a situation that | using numbers, starting from data collection, discovery of that data as well as its appearance and results. Analytical research emphasizes numerical data (numbers processed using statistical methods). The results of this research show that the influence of transformative leadership has a significant influence on the quality of Human Resources at the Seberang Village Office, Bone Regency. Based on the significance value (Sig.) of 0.014, it is known that the significance value (Sig.) is smaller than 0.05, so it can be concluded that H1 is accepted. Apart from that, it is known that the regression coefficient is 0.171, which means that for every 1% increase in the level of influence of Transformative Leadership, Human Resources will increase by 0.171. Furthermore, because the regression coefficient value is positive (+), it can be said that TransformativeLeadership has a positive effect on Human Resources. This positive influence means that as Transformative Leadership increases in the Seberang Village Office, it will have an effect on increasing Human Resources in the Seberang Village Office, Bone Regency.Keywords: Transformative Leadership, Leader, Human Resources